Pola Pertumbuhan Ikan Swanggi (Priacanthus tayenus Richardson, 1846) di Perairan Makassar - Kantun, Wayan; Permatasari, Intan; Wulandari, Sri (Jurnal Riset Diwa Bahari (JRDB), 2024)
Purple-spotted bigeye is an economically important fish that is widely used by the community, resulting in intensive fishing and is thought to have caused pressure on resources which has an impact on changes in its biological structure. Based on this, research needs to be carried out to determine the size distribution, growth patterns and condition factors of Purple-spotted bigeye in the waters of the Makassar Strait. This research was carried out from April to June 2024 at the Paotere Makassar, Maros, and Macini Baji Fish Landing Sites in Pangkajene and the Islands. This research is classified as a quantitative type of research with survey methods and direct measurements in the field. The number of samples that were successfully measured was 725 fish, a combination of male and female fish with representation in small, medium and large sizes. Fish were measured to the length of the fork and weighed to determine the total weight of the fish. The results showed that the growth pattern of purple-spotted bigeye was negative allometric with b value of 1.4147 (b < 3) with length increase faster than weight increase, condition factor ranging from 0.242 to 2.837 (1.063 ± 0.379) and distribution of fork lengths around 34 .2-98.8 mm (72.44 ± 9.32 mm) with a weight ranging from 0.46-88.6 mg (34.27 ± 13.44 mg). Based on the value of the growth pattern, the purple-spotted bigeye is included in a condition of stressed resources.